Professional IIS 7 and ASP.NET integrated programming - Khosravi, Shahram, 1963- (Wrox professional guides., 2008)
The deep integration of IIS7 and ASP.NET provides both IIS7 administrators and ASP.NET developers with new and exciting programming tools, techniques, and approaches that were not possible with earlier versions of IIS. With this book, Dr. Shahram Khosravi.